1985
DOI: 10.1159/000242145
|View full text |Cite
|
Sign up to set email alerts
|

Nonmigrating Rhythmic Activity in the Stomach and Duodenum of Neonates

Abstract: We studied gastrointestinal motility in 20 infants, using a modified manometric method for neonates, and compared it to that in adults. Changes in the intragastric and intraduodenal pressures were recorded for 3 h after the ingestion of milk. Bands of contractions with the same rhythmicity as phase III activity in adults were frequently recorded. Some of them migrated caudally and were speculated to be the equivalent of phase III activity of the interdigestive migrating complex (IMC) in adults. However, others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 5 publications
4
32
0
1
Order By: Relevance
“…These data were compatible with studies in humans, showing that the intraluminal pressures achieved in the stomach are greater in adults compared to neonates (2). The age-related changes in gastric smooth muscle physiology that are responsible for increasing contraction have not been examined.…”
supporting
confidence: 82%
“…These data were compatible with studies in humans, showing that the intraluminal pressures achieved in the stomach are greater in adults compared to neonates (2). The age-related changes in gastric smooth muscle physiology that are responsible for increasing contraction have not been examined.…”
supporting
confidence: 82%
“…Although premature neonates have been noted to be more likely than term neonates to suffer from feed intolerance, regurgitation and gastro‐oesophageal reflux, the causes of this may be altered feedback from the proximal small intestine and intolerance to the high fat content of preterm infant formulas rather than any impairment of gastric motility 25, 26, 27. Lange et al .…”
Section: Introductionmentioning
confidence: 99%
“…The relatively low feeding volume during the first hours of life, coinciding with the physiologic diuresis of excess extracellular fluid that accompanies the transition from prenatal to postnatal life, may be caused by one or more factors, including a lack of hunger or thirst because of CNS depression or arousal, changing hormone concentrations associated with parturition, or immaturity of gastric function. Despite the appearance of anatomic features of the digestive tract early in fetal life (1, 2), many aspects of gastrointestinal motility are immature in the neonate (3)(4)(5)(6). In vitro studies demonstrated rapid postnatal changes in the receptors (7,8) and responses to agonists in rabbit gastric muscle (9,10).…”
mentioning
confidence: 99%